#### Answer

$\displaystyle \frac{x(3y-2)}{2y+x}$

#### Work Step by Step

Numerator:
$\displaystyle \frac{3}{x}-\frac{2}{xy}$=$\displaystyle \frac{3}{x}\cdot\frac{y}{y}-\frac{2}{xy} =\frac{3y-2}{xy}$
Denominator:
$\displaystyle \frac{2}{x^{2}}+\frac{1}{xy}=\frac{2}{x^{2}}\cdot\frac{y}{y}+\frac{1}{xy}\cdot\frac{x}{x}=\frac{2y+x}{x^{2}y}$
Convert Numerator $\div$ Denominator to multiplication
$\displaystyle \frac{3y-2}{xy}\cdot\frac{x^{2}y}{2y+x}=\quad$... cancel common factors, $x, y$
$=\displaystyle \frac{x(3y-2)}{2y+x}$